Circ_0093887 upregulates CCND2 and SUCNR1 to inhibit the ox‐LDL‐induced endothelial dysfunction in atherosclerosis by functioning as a miR‐876‐3p sponge. (29th April 2021) - Gao, Yanhui; Li, Guangnan; Fan, Shasha; Wang, Yu; Wei, Hong; Li, Mingyang; Li, Xueqi
Abstract: Circular RNAs (circRNAs) are widely expressed in mammals and act as regulatory targets in the atherogenesis. The objective of this study was to research the biological role and molecular mechanism of circ_0093887 in oxidized low‐density lipoprotein (ox‐LDL)‐induced atherosclerosis (AS) of human aortic endothelial cells (HAECs). Cell viability detection was performed by CCK‐8 assay. Inflammatory molecules were examined using ELISA. Flow cytometry was used to measure cell‐cycle progression and cell apoptotic rate. Caspase 3 activity was determined using caspase 3 activity assay. The expression levels of circ_0093887, miR‐876‐3p, CCND2 and SUCNR1 were assayed by quantitative real‐time polymerase chain reaction (qRT‐PCR). Dual‐luciferase reporter, RNA immunoprecipitation (RIP) and RNA pull‐down assays were used for the target analysis. EdU assay, wound healing assay/transwell assay and tube formation assay were, respectively, used to assess the effects of circ_0093887/miR‐876‐3p axis on cell proliferation, migration and tube formation. Oxidized low‐density lipoprotein inhibited cell viability and cell‐cycle progression but induced the inflammatory response and cell apoptosis. Circ_0093887 was downregulated and miR‐876‐3p was upregulated in AS patients and ox‐LDL‐treated HAECs. Functionally, the overexpression of circ_0093887 abrogated the cell injury of HAEC exposed to ox‐LDL. For the functional mechanism, we found that circ_0093887 was a sponge for miR‐876‐3p and miR‐876 targeted CCND2 or SUCNR1. The reverted experiment indicated that the function of circ_0093887 was achieved by sponging miR‐876‐3p. Meanwhile, miR‐876‐3p inhibitor relieved the inhibitory regulation of circ_0093887 knockdown in cell proliferation, migration and tube formation. Downregulation of miR‐876‐3p also alleviated the ox‐LDL‐induced cell injury by upregulating the expression of CCND2 or SUCNR1. Furthermore, circ_0093887 was validated to regulate the levels of CCND2 and SUCNR1 via the sponge effect on miR‐876‐3p. The protective effects of circ_0093887 on HAECs from ox‐LDL were also ​alleviated by repressing the CCND2 and SUCNR1 levels. These findings suggested that circ_0093887 protected HAEC against the ox‐LDL‐induced inflammatory and apoptotic damages by targeting the miR‐876‐3p/CCND2 or miR‐876/SUCNRA axis. Circ_0093887 could act as a potential therapeutic biomarker for AS patients.